The made in China challenge to US structural power: industrial policy, intellectual property and multinational corporations. Issue 2 (4th March 2022) - Malkin, Anton
Abstract: This paper addresses the question of United States' power in the global economy, suggesting that China's structural power potential vis-à-vis its American counterpart has been underestimated in recent international political economy (IPE) literature. It examines the US-China trade and technological conflict and maps China's autonomy and influence in the global economy, offering a new interpretation of structural power, assessed on the basis of the growing importance of intangible assets in global value chains. The paper focuses on the notion of productive power, expanding on Susan Strange's definition of productive power by breaking down this category of power into four subcategories: 1) centrality in global value chains, 2) market power, 3) ownership of assets, and 4) technological standard-setting. The paper begins by framing the US-China tech and trade confrontation in terms of a relative power contest between the two superpowers. Examining data and literature on China's ascent in the realm of intellectual property protection and commercialization, global value chain ascension, as well as standard setting and competition policy, it points to China's growing strengths in each of these categories, respectively. It concludes that China possesses latent productive power, and that the Made in China 2025 and related industrial policy plans aim to actualize China's structural power potential.